DOI: 10.1007/0-387-32957-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Serological Diagnosis of Human Polyomavirus Infection

Abstract: Measurement of antibody titres to the human polyomaviruses BK and JC has for many years had to rely on Haemagglutination inhibition. In recent years, viral serology based on viruslike particles (VLPs) in enzyme immunoassays (EIAs) has become widely used for a variety of viruses. We sought to establish a modern method for serological diagnosis of BK and JC viruses, by using purified yeast-expressed virus like particles (VLP) containing the VP1 major capsid proteins. Antibody titres in assays based on VLPs of BK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 21 publications
(3 reference statements)
3
23
0
1
Order By: Relevance
“…Anti-agnoprotein IgG was detected in only 15% and 7.5% of HD and KT patients, respectively, which was significantly lower than the 63% and 80% seropositivity for VP1 and the 42% and 62% seropositivity for LTD1, respectively. In adult populations similar to our study groups, BKV seroprevalence rates of between 60 and 90% have been reported using assays which detect antibody responses directed against the major capsid protein VP1 by EIA or by inhibiting its interaction with receptor-like glycosylated surface structures of type O erythrocytes, i.e., by hemagglutination inhibition (18,23,25,32). The higher VP1-type response may partly be due to the fact that the host immune system is more readily and even systemically (re)exposed to viral surface proteins which typically contain neutralizing epitopes (11).…”
Section: Discussionsupporting
confidence: 80%
“…Anti-agnoprotein IgG was detected in only 15% and 7.5% of HD and KT patients, respectively, which was significantly lower than the 63% and 80% seropositivity for VP1 and the 42% and 62% seropositivity for LTD1, respectively. In adult populations similar to our study groups, BKV seroprevalence rates of between 60 and 90% have been reported using assays which detect antibody responses directed against the major capsid protein VP1 by EIA or by inhibiting its interaction with receptor-like glycosylated surface structures of type O erythrocytes, i.e., by hemagglutination inhibition (18,23,25,32). The higher VP1-type response may partly be due to the fact that the host immune system is more readily and even systemically (re)exposed to viral surface proteins which typically contain neutralizing epitopes (11).…”
Section: Discussionsupporting
confidence: 80%
“…Seropositivity for JCV was first determined using hemagglutination inhibition assays, but this has since been replaced by enzyme-linked immunosorbent assays (ELISAs), using recombinant VLPs (182,290). More recently, a two-step anti-JCV antibody assay has been developed in an attempt to stratify disease risk by antibody presence.…”
Section: Analysis Of the Viral Genomementioning
confidence: 99%
“…The most common method for studying seroprevalence of polyomaviruses is enzyme-linked immunosorbent assay (ELISA) using VP1 capsomers or VP1-based virus-like particles (VLPs) as the capture antigen [e.g. (15)(16)(17)(18)(19)(20)(21)(22)(23)]. Of these two possibilities, VLP-based ELISA is likely more sensitive as VP1 VLPs morphologically resemble mature infectious particles and thus present conformational epitopes (24).…”
Section: Seroepidemiology Of the Novel Hpyvsmentioning
confidence: 99%